Banking sector stability and foreign direct investment inflows in Ghana - ASANTE WILLIAM (knust, 2024)
A thesis submitted to department of accounting and finance, Kwame Nkrumah university of science and technology, Kumasi In partial fulfillment of the requirement for the degree of master of science (accounting and finance option) school of business college of humanities and social sciences